Assessing the risk of under-deposit chloride-induced stress corrosion cracking in austenitic stainless steel nuclear waste containers. (September 2014) - Cook, A. B.; Lyon, S. B.; Stevens, N. P. C.; Gunther, M.; McFiggans, G.; Newman, R. C.; Engelberg, D. L.
<x content-type="archive" xml:space="preserve">Abstract</x> This paper provides a short summary of investigations that have focused on the occurrence of the phenomenon that is commonly referred to as atmospheric chloride-induced stress corrosion cracking (AISCC) in types 304L and 316L austenitic stainless steels; the materials from which storage containers for the UK's intermediate level nuclear waste are currently fabricated. A brief overview of the relationship between localised corrosion phenomena (pitting or crevice corrosion) and stress corrosion cracking from observations derived under conditions of immersion in chloride-containing environments is provided. The impact of environmental variables such as the relative humidity, temperature and chloride deposition density on the development of AISCC and potential difficulties in extrapolating data derived from laboratory investigations to an in-store situation are also discussed. Proposals for the development of laboratory protocols that may more accurately reflect behaviour in an actual storage situation, including the possibility of employing accelerated testing methods, are also briefly addressed.